2022
DOI: 10.1186/s13244-022-01300-w
|View full text |Cite
|
Sign up to set email alerts
|

Application of deep learning reconstruction of ultra-low-dose abdominal CT in the diagnosis of renal calculi

Abstract: Background Renal calculi are a common and recurrent urological disease and are usually detected by CT. In this study, we evaluated the diagnostic capability, image quality, and radiation dose of abdominal ultra-low-dose CT (ULDCT) with deep learning reconstruction (DLR) for detecting renal calculi. Methods Sixty patients with suspected renal calculi were prospectively enrolled. Low-dose CT (LDCT) images were reconstructed with hybrid iterative rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In the study of Zhang et al [ 31 ] which used the same vendor as our study, the mean CT values of the liver parenchyma on non-injected DLR was slightly superior to those of hybrid-IR (57.70 ± 8.36 vs 56.30 ± 8.87, respectively) but the difference was not statistically significant ( P = .389). These results are consistent with our data, as all these studies showed a significantly increased SNR with DLR than with hybrid IR, in addition to better image quality and a lower radiation dose.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In the study of Zhang et al [ 31 ] which used the same vendor as our study, the mean CT values of the liver parenchyma on non-injected DLR was slightly superior to those of hybrid-IR (57.70 ± 8.36 vs 56.30 ± 8.87, respectively) but the difference was not statistically significant ( P = .389). These results are consistent with our data, as all these studies showed a significantly increased SNR with DLR than with hybrid IR, in addition to better image quality and a lower radiation dose.…”
Section: Discussionmentioning
confidence: 54%
“…Only 2 papers have used the same vendor as the one we used (Canon Medical Systems). [ 31 , 32 ] A possible explanation for this apparent disagreement with the results between all published papers could be the type of vendor used, with its specific DLR algorithm. In the DLR, the quality of the training target determines the performance of the output.…”
Section: Discussionmentioning
confidence: 92%
“…DLIR has been applied to a wide range of CTA protocols like chest, abdominal and vascular diseases, exhibiting 13.6–37.6% reduction in image noise ( 19 , 31 - 33 ). Our study utilized DLIR-H algorithm to reconstruct one-stop CTA images for the first time and demonstrated its superiority again in preserving image quality under low radiation and contrast dose settings.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, deep learning has been applied to low-dose or ultra-low-dose CT denoising. Despite the significant dose reduction achieved with ultra-low dose CT, diagnostic performance for urolithiasis remained excellent using two vendor-specific deep learning imaging reconstruction algorithms (TrueFidelity in GE Healthcare and Advanced intelligent Clear-IQ Engine in Cannon Medical System) [ 24 ]. It was consistent with this study in terms of deep learning imaging reconstruction.…”
Section: Discussionmentioning
confidence: 99%